2013
DOI: 10.1039/c3ta11598d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al-doping on the properties of Li–Mn–Ni–O cathode materials for Li-ion batteries: an ab initio study

Abstract: The key properties of a successful cathode material, such as the structural stability during delithiation, the battery voltage, and the Li mobility, were investigated for Al-doped Li-Mn-Ni oxide structures, using density-functional theory and the nudged-elastic band method. The rhombohedral layered structure of LiMn 0.5 Ni 0.5 O 2 with zigzag and flower arrangements of transition metal atoms as well as the monoclinic structure of Li(Li 1/6 Ni 1/6 Mn 2/3 )O 2 were used as base structures. A stabilizing effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 40 publications
1
72
0
Order By: Relevance
“…37 In a detailed theoretical study, Dianat et al studied the effect of Al doping on Li-Mn-Ni-O based cathode materials. 38 They reported that Al doping stabilizes the partially intercalated states, but increases the Li-diffusion barriers. Park et al studied Al doping in LiNiO 2 , and they found improved cycling behavior at high temperatures due to Al-doping.…”
mentioning
confidence: 99%
“…37 In a detailed theoretical study, Dianat et al studied the effect of Al doping on Li-Mn-Ni-O based cathode materials. 38 They reported that Al doping stabilizes the partially intercalated states, but increases the Li-diffusion barriers. Park et al studied Al doping in LiNiO 2 , and they found improved cycling behavior at high temperatures due to Al-doping.…”
mentioning
confidence: 99%
“…12,22,26 No γ-LiAlO 2 or Al 2 O 3 peaks were detected, showing that the material was phase pure. The average particle size was calculated to be ∼50 nm.…”
Section: Resultsmentioning
confidence: 99%
“…While investigations into using chromium 19,20 and ruthenium 21 have been carried out, one potentially particularly attractive dopant is comparatively inexpensive aluminum. A computational study 22 has suggested that a small degree of aluminum doping should have a stabilizing effect on the structure, resulting in a decrease in voltage fade. In addition, aluminum doping has been shown to improve the thermal stability of lithium-manganese rich composites at low cycling rates, though this improvement is sometimes accompanied by a corresponding decrease in capacity.…”
mentioning
confidence: 99%
“…Up to now, extensive measures have been conducted to ameliorate the properties of LNCM, including doping (e.g. Ti and Al), [13,14] coating (e.g. Li 2 TiO 3 and Al 2 O 3 ) [2,15] and fabricating special morphology of LNCM (e.g.…”
Section: Introductionmentioning
confidence: 99%